2018
DOI: 10.1177/0897190018799261
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Nephrotoxicity Associated With Nonrenally Adjusted Intravenous Polymyxin B Compared to Traditional Dosing

Abstract: Background: Polymyxin B’s package insert recommends renal adjustment. Contemporary studies suggest it does not require renal adjustment. Objective: To determine whether time to acute kidney injury (AKI) differs between renally adjusted and nonadjusted intravenous (IV) polymyxin B. Methods: This retrospective chart review compared time to AKI after renally adjusted and nonadjusted IV polymyxin B administration. It included patients who were 18 years or older, received IV polymyxin B, and had creatinine clearanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The pathogenesis of AKI in severe infection or sepsis is highly related to renal hypoperfusion derived from the toxic effects of inflammation and impaired microcirculation[34]. A single-center, retrospective study with 54 patients was implemented by Maniara et al also obtained a similar result that subtherapeutic doses from renal adjustment could lead to unresolved infections and a higher incidence of AKI[35]. In consequence, renal dosing adjustment of PMB is unnecessary for patients with kidney function impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of AKI in severe infection or sepsis is highly related to renal hypoperfusion derived from the toxic effects of inflammation and impaired microcirculation[34]. A single-center, retrospective study with 54 patients was implemented by Maniara et al also obtained a similar result that subtherapeutic doses from renal adjustment could lead to unresolved infections and a higher incidence of AKI[35]. In consequence, renal dosing adjustment of PMB is unnecessary for patients with kidney function impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Peyko et al found that patients who received renally adjusted PMB doses owned higher LOS and mortality due to PMB underdose against infection[36]. Research from Maniara et al showed that renal dose adjustment of PMB did not affect microbiological cure, clinical cure, or 30-day mortality[35]. In this aspect, dosing without renal adjustment is a proper PMB dosing strategy to increase the probability of meeting the therapeutic target and get a better curative rate ultimately.…”
Section: Discussionmentioning
confidence: 99%
“…The organisms most commonly identified in CR-GNB infections are Klebsiella pneumoniae , Acinetobacter baumannii , and Pseudomonas aeruginosa [ 2 4 ]. These bacteria can lead to bloodstream, respiratory tract, skin and soft tissue, urinary tract, intra-abdominal, and surgical infections [ 3 , 5 7 ]. They are responsible for nosocomial infections, particularly among critically ill patients hospitalized in intensive care units (ICUs) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The organisms most commonly identi ed in CR-GNB infections are Klebsiella pneumoniae, Acinetobacter baumannii, and Pseudomonas aeruginosa [2][3][4]. These bacteria can lead to bloodstream, respiratory tract, skin and soft tissue, urinary tract, intra-abdominal, and surgical infections [3,[5][6][7]. They are responsible for nosocomial infections, particularly among critically ill patients hospitalized in intensive care units (ICUs) [8].…”
Section: Introductionmentioning
confidence: 99%